2005
DOI: 10.1291/hypres.28.953
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Compliance with Salt Restriction in Japanese Hypertensive Patients

Abstract: The purpose of the present study was to investigate the long-term compliance with salt restriction in Japanese hypertensive patients. Subjects included 389 patients, 230 women and 159 men, mean age 58 ± 11 years, who underwent successful 24-h home urine collection more than three times over an interval of a year. Urinary salt, potassium, and creatinine were measured. Additionally, family history, habitual alcohol intake, smoking habit, physical activities, and job status were assessed by use of a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 17 publications
(10 reference statements)
4
16
0
1
Order By: Relevance
“…[3][4][5] In addition, reducing salt intake can be difficult in medical practice. Ohta et al 13 demonstrated that the rate of achievement of an average urinary salt excretion of o6 g per day, with instructions to reduce salt intake from trained dieticians, was only 10.3%, which was similar to the results of the present study (11.3%). Actually, the average daily salt excretion achieved in this study was 8.7 g per day, which is much greater than that recommended by several guidelines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[3][4][5] In addition, reducing salt intake can be difficult in medical practice. Ohta et al 13 demonstrated that the rate of achievement of an average urinary salt excretion of o6 g per day, with instructions to reduce salt intake from trained dieticians, was only 10.3%, which was similar to the results of the present study (11.3%). Actually, the average daily salt excretion achieved in this study was 8.7 g per day, which is much greater than that recommended by several guidelines.…”
Section: Discussionsupporting
confidence: 91%
“…First, the estimation of daily urinary salt excretion using a spot urine sample might be less accurate than that using 24-h urine collection, as mentioned above. However, the changes in urinary salt excretion obtained in this study using spot urine were very similar to those assessed with 24-h urine collection by Ohta et al 13 (9.6 ± 4.2 to 8.7 ± 3.4 g per day). Second, this study focused on mid-term results, thus the long-term results are not known.…”
Section: Limitationssupporting
confidence: 88%
“…12,31,32 In the literature, people employed in regular jobs are involved in physical activity more than those who are unemployed. 33 In the present study, similar to the literature, the rate of adherence to physical activity was high in the male participants and in those who perceived their income level as good.…”
Section: Discussionmentioning
confidence: 99%
“…11 Long-term compliance with salt restriction in hypertensive patients was also extremely low. 12 As it is difficult to change dietary habits in adults, education or intervention to reduce salt intake during childhood is very important. However, there are very few studies addressing salt intake in Japanese children.…”
Section: Introductionmentioning
confidence: 99%